Niðrstigningar saga : Sources, Transmission, and Theology of the Old Norse "Descent into Hell." - Bullitta, Dario (Toronto Old Norse-Icelandic Series (TONIS), 2018)
Dario Bullitta has embarked on a highly fascinating voyage that traces the routes of transmission of the Latin "Evangelium Nicodemi" text to Iceland and continental Scandinavia.